Human papillomavirus-related oropharyngeal carcinoma. (5th April 2022) - Saito, Yuki; Homma, Akihiro; Kiyota, Naomi; Tahara, Makoto; Hanai, Nobuhiro; Asakage, Takahiro; Matsuura, Kazuto; Ota, Ichiro; Yokota, Tomoya; Sano, Daisuke; Kodaira, Takeshi; Motegi, Atsushi; et al.
Abstract: It was not until around 2000 that human papillomavirus-related oropharyngeal carcinoma was recognized as carcinoma with clinical presentations different from nonrelated head and neck carcinoma. Twenty years after and with the revision of the tumor–node–metastasis classification in 2017, various clinical trials focused on human papillomavirus-related oropharyngeal carcinoma to improve the prognosis and quality of life of patients with this disease. However, the incidence of human papillomavirus-related cancers is increasing, which is expected to be particularly prominent in Japan, where human papillomavirus vaccination is not widely available. In this review, we describe the current status of clinical trials (mainly focused on initial surgery and radiation dose reduction) for, primary and secondary prevention of, and the present status of human papillomavirus-related oropharyngeal carcinoma in Japan. Abstract : This review provides a clear summary of the current knowledge on human papillomavirus-related oropharyngeal carcinoma. The current standard of care for this disease is RT with CDDP and surgery. We believe that surgical treatment is best indicated for patients eligible for CDDP-RT when postoperative adjuvant therapy can be omitted. HPV-OPSCC prevention is urgently needed in Japan, where the HPV vaccination rate is low and the possibility of an increase in the incidence of HPV-OPSCC is high.